Research progress on application of the trans-theoretical model and stages of change in standard precautions among nurses - YIN, Hongmei (Chinese Journal of Integrative Nursing, 2022)
This paper reviewed the concept, content, intervention strategy, intervention significance of the trans-theoretical model and stages of change and its application in standard precautions among nurses, and summarized its application effect, aiming to provide reference for establishing the guidance of standard precautions for clinical nurses. (本文对行为阶段转变理论概念、内容、干预策略、干预意义及在护士准防护中应用现状进行综述, 总结分析其应用效果, 以期为临床护士标准防护指导提供参考依据。)